Pendidikan Kristiani sebagai Instrumen Penyadaran Pentingnya Pertumbuhan Spiritualitas dalam Konteks Budaya Populer - Daniel Syafaat Siahaan (Faculty of Theology Duta Wacana Christian University, 2016)
Abstract This article is written based on my observation and experience, who